PERLINDUNGAN HUKUM TERHADAP PESERTA ARISAN ONLINE AKIBAT WANPRESTASI YANG DILAKUKAN OLEH OWNER - Raihan Erji Yoshio Wijaya (Fakultas Hukum Universitas Udayana, 2024)
This research is aimed at finding out the legal relationship between online social gathering participants and online social gathering owners in terms of the Civil Code and knowing the legal protection for online social gathering participants who suffer losses due to breach of contract committed by the owner. This research was conducted using normative juridical research methods with qualitative descriptive analysis methods. The first research result obtained was that the legal relationship between online social gathering participants and the online social gathering owner must be based on the applicable provisions in the Civil Code, namely Article 1338 and Article 1320, this is to avoid acts of breach of contract by the online social gathering owner at any time. The results of the second research explained that legal protection for online social gathering participants from acts of breach of contract by online social gathering owners can be done in two ways, namely through litigation or non-litigation as an effort to obtain compensation and in a fair manner.